A Study on the Operating Systems for Low End IOT Devices - R, Anusha; Soundarya, B; Priyanka, G; Soniya, V. (International Journal of Engineering and Technology, 2018)
The IOT interconnect billions of devices and they can be connected to internet. IOT run on high end devices which use traditional operating systems like Linux and low end devices with less computational power, memory etc. The large scale deployment of the system will need appropriate OS for the development, deployment and maintenance of the devices. In this paper we research on OS that could run on low end devices for IOT.Â